2018
DOI: 10.1038/s41467-018-04413-3
|View full text |Cite
|
Sign up to set email alerts
|

Specific stereochemistry of OP-1074 disrupts estrogen receptor alpha helix 12 and confers pure antiestrogenic activity

Abstract: Complex tissue-specific and cell-specific signaling by the estrogen receptor (ER) frequently leads to the development of resistance to endocrine therapy for breast cancer. Pure ER antagonists, which completely lack tissue-specific agonist activity, hold promise for preventing and treating endocrine resistance, however an absence of structural information hinders the development of novel candidates. Here we synthesize a small panel of benzopyrans with variable side chains to identify pure antiestrogens in a ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 52 publications
(67 reference statements)
1
72
0
Order By: Relevance
“…S1F). To our surprise, the side chain of [F]-OC2-Pip (19) did not point towards h12, but instead exited between h8 and h11, where it is stabilized by H-bonds with h11 His524 (Fig. 1D, Fig.…”
Section: Ringmentioning
confidence: 84%
See 2 more Smart Citations
“…S1F). To our surprise, the side chain of [F]-OC2-Pip (19) did not point towards h12, but instead exited between h8 and h11, where it is stabilized by H-bonds with h11 His524 (Fig. 1D, Fig.…”
Section: Ringmentioning
confidence: 84%
“…To test whether the compounds were effective against the constitutively active Y537S-ER that drives treatment-resistant metastatic disease and reduces the potency of antiestrogens, we tested the compounds with this receptor. Several of the piperidines were very efficacious (16)(17)(18)(19), as were the [F]-AcrEster and [F]-RU compounds (21 and 27) ( Fig. 1G-H, Fig.…”
Section: Dmeri Show Ligand Selective Activity Profiles In Other Cellumentioning
confidence: 99%
See 1 more Smart Citation
“…The gold standard treatment in this type of BC is the hormone adjuvant therapy, which either suppresses estrogen production (aromatase inhibitors) or modulates/degrades the ERα (SERMs/SERDs). The prolonged exposure to these therapies, usually administered consecutively for 5–10 years' time-frame, leads to resistance in half of all luminal BCs after 5 years, in spite of the ERα expression (Toy et al, 2017; Fanning et al, 2018; Busonero et al, 2019; Spinello et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapy counteracting mERα is a current object of intense preclinical and early clinical interest, as also evidenced by the significant number of studies aiming at identifying orally bioavailable SERDs, eventually able to overcome resistance (De Savi et al, 2015; Fanning et al, 2018; Hamilton et al, 2018; Sharma et al, 2018; Kahraman et al, 2019; Scott et al, 2019). Among these GDC-810, AZD9496 ( 5 ; Figure 1) (hereafter AZD, a drug in preclinical use as oral SERD, for which a first clinical study have been recently accomplished) (Weir et al, 2016; Hamilton et al, 2018), and LSZ102 have been identified (Scott et al, 2019).…”
Section: Introductionmentioning
confidence: 99%